Cover Picture: 2D Inorganic–Antimalarial Drug–Polymer Hybrid with pH‐Responsive Solubility (Chem. Asian J. 10/2015). Issue 10 (23rd September 2015) - Kim, Ji‐Yeong; Yang, Jae‐Hun; Lee, Ji‐Hee; Choi, Goeun; Park, Dae‐Hwan; Jo, Mi‐Rea; Choi, Soo‐Jin; Choy, Jin‐Ho
<x xml:space="preserve">Abstract</x> Artesunate is a widely used antimalarial drug. It has very low toxicity and side effects, but its fragility in gastric solution, poor solubility, and short in vivo half‐life result in very low bioavailability. In their Full Paper on page 2264, Jin‐Ho Choy et al. report on a novel drug delivery system (DDS) to improve the bioavailability in oral administration. The new enteric coating formulation consists of polymer and 2D inorganic carrier intercalated with artesunate, and the resulting DDS shows pH‐responsive release, enhanced aqueous solubility, sustained plasma concentration, and eventually very high bioavailability.